2019
DOI: 10.1002/ejp.1438
|View full text |Cite
|
Sign up to set email alerts
|

Masseter corticomotor excitability is decreased after intramuscular administration of nerve growth factor

Abstract: Background Quantification of motor‐evoked potentials (MEPs) can contribute to better elucidate the central modulation of motor pathways in response to nociceptive inputs. The primary aim of this study was to assess the modulatory effects of nerve growth factor (NGF) injection on masseter corticomotor excitability. Methods The healthy participants of this randomized, double blind placebo‐controlled experiment were assigned to have injected into the right masseter muscle either NGF (n = 25) or isotonic saline (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“… 7 , 17 In-depth investigations revealed that NGF played an important role in pain modulation. 18 Local administration of NGF could elicit pain and neutralizing antibody against NGF could significantly alleviate pain, 8 rendering neutralizing antibody treatment against NGF a good pain-relief option in clinical practice. 19 Released by local injured tissues, NGF elicits profound inflammatory reactions that ultimately cause painful sensations.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 17 In-depth investigations revealed that NGF played an important role in pain modulation. 18 Local administration of NGF could elicit pain and neutralizing antibody against NGF could significantly alleviate pain, 8 rendering neutralizing antibody treatment against NGF a good pain-relief option in clinical practice. 19 Released by local injured tissues, NGF elicits profound inflammatory reactions that ultimately cause painful sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hodges highlighted that the nuances of the motor system adaptation to pain were affected by individual variations and motor task differentiation 20,21 . And now, surface electromyography (EMG), 22 motor‐evoked potentials (MEPs) and transcranial magnetic stimulation (TMS) have been used to evaluate the relationship among oro‐facial pain, muscle function state and the activity and function of specific brain circuits 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…After cleaning the skin with alcohol, a sterile solution of recombinant human NGF (dose of 5 μg [0.2 mL]) will be given as a bolus injection into the right masseter on days 0 and 2 using a 1-mL syringe with a disposable needle (27 G). Following the procedure of Costa et al, 4 the needle will be inserted perpendicular to the masseter body until bony contact. The needle will then be retracted ∼2 mm, aspiration performed, and NGF injected.…”
Section: Methodsmentioning
confidence: 99%